Influence of Tunnel Excavation on the Deformation of a Frame Building - Yang Li; Guangyi Zhou; Tianjiao Li; Chun’an Tang; Bin Gong; Kaikai Wang (Buildings, 2023)
Tunnel excavation inevitably causes surface deformation. In urban areas, surface deformation could lead to the deformation of surrounding buildings, which may cause damage to communities when accumulated to a certain extent. However, the current construction organization and management mainly rely on on-site deformation measurements, and there is still a lack of reliable prediction methods. Here, we proposed an effective evaluation method for frame building deformation based on the stochastic medium theory and the equivalent beam theory. This method could effectively evaluate the surface and building deformation after a horseshoe tunnel excavation by considering the non-uniform convergence. Furthermore, its accuracy and practicability were verified using the Nanyan Fourth Circuit Transmission Reconstruction located in Dalian, China. The results show that the spatial distribution and characteristic values of the maximum tensile strains were closely related to the ratio of Young’s modulus to the shear modulus (E/G), the building height (h), the tunnel depth (H), the tangent of the tunnel influence angle (tan β) and the convergence radius (ΔR). These achievements can provide a theoretical basis and analytical ideas for investigating the influence of shallow buried tunnel excavation on frame structure buildings in cities.